Evaporites in Central Lapland Greenstone Belt - Haverinen, Juho (Helsingin yliopisto, 2020)
Paleoproterotzoic evaporitic rocks in the Central Lapland Greenstone Belt (CLGB) were discovered in 2016 as a result of relatively deep diamond core drilling (400-1100m) during a Ni-Cu-PGE ore exploration project. Evaporites occur as relatively flat successions. Highly soluble evaporites were probably initially preserved by active magmatism that enveloped these layers under extrusives or/and in between subvolcanic sills. Under the deformation the plastic behaviour of evaporites may have provided a platform that may have functioned as a slip surface for the prograding thrust faults. Plastic behaviour may also have prevented folding. Evaporites in the Central Lapland Greenstone Belt formed after the Great Oxidation Event, during the late stages of Lomagundi-Jatuli carbon isotope event. The discovered evaporites belong to the Savukoski Group rocks (2.2-2.05 Ga) that resemble a closing rift and the corresponding of a shallow sea environment, where evaporites are considered to have precipitated by oversaturation induced by anomalously high terrestrial influx that was enhanced by newly introduced oxic conditions. Age constraints for these deposits are provided by their relative position in the CLGB stratigraphy: 1. They postdate the appearance of fist black shales of the Matarakoski Formation in Kitinen and Siuliunpalo Formation in Pelkosenniemi (<2.2 Ga), and 2. they predate the ultramafic volcanic rocks of the Sattasvaara Formation in Kitinen and Kummitsoiva Formation in Pelkosenniemi (>2.05Ga). These conclusions are strengthened by carbon isotope results from carbonates. Evaporitic carbonates show elevated 13C values ranging from +4 to +14 ‰, with an average at +9 ‰. These values correlate well with the timing of the Paleoproterotzoic carbon excursion (2.2-2.06 Ga). The excursion has been addressed to extensive burial of organic carbon (Karhu & Holland, 1996). 34S values form a relative tight group between +5 -+8 ‰ (averaging +6.5 ‰) and are similar with the roughly coeval Paleoproterotzoic evaporitic ...